Terapias alternativas para o tratamento da estomatite por prótese total: Modelo experimental in vivo em ratos - Teodoro, Guilherme Rodrigues [UNESP]; Lima, Gabriela de Morais Gouvêa [UNESP]; Silva, Marina Bacelar [UNESP]; Lopes, Patrícia Carla [UNESP]; Hiraoka, Cybelle Mori [UNESP]; Santana-Melo, Gabriela de Fátima [UNESP]; Pereira, Daniel Freitas Alves [UNESP]; Brighenti, Fernanda Lourenção; Koga-Ito, Cristiane Yumi [UNESP] (Editora Cubo, 2017)
Background: Denture stomatitis (DS) is a multifactorial condition that commonly affects denture users and is mainly caused by Candida albicans. Due to the toxic effects of antifungal therapy, new therapies for DS are claimed. Objective: The aim of the study was to evaluate the efficacy of aqueous extract of Buchenavia tomentosa and sodium bicarbonate against C. albicans in a model of DS in rats. Material and Methods: An acrylic resin device simulating a denture base was fixed covering the palate of forty-eight male rats followed by candidiasis induction. Rats were divided into 4 groups (n = 12): Control, sodium bicarbonate, B. tomentosa and nystatin (positive control). Each group was subdivided according to the period of treatment; 24 h (n = 6) and 48 h (n = 6). Animals were sacrificed and had their devices removed for C. albicans counts and SEM analysis. The palate mucosa was removed and processed for histopathologic analysis. Results: After 24 h of treatment, both B. tomentosa and nystatin groups reduced significantly C. albicans counts when compared to control (nystatin x control, p < 0.01; B. tomentosa x control, p = 0.03). The results were confirmed by the histologic analysis. Conclusion: Both the aqueous extract of B. tomentosa and sodium bicarbonate was able to significantly decrease C. albicans counts in an experimental model of DS.
Alternative therapies for denture stomatitis treatment: In vivo experimental model in rats
Keywords: Alternative; Buchenavia tomentosa; Candida albicans; Denture; Stomatitis; Therapies